Cannabis‐dependent adolescents show differences in global reward‐associated network topology: A functional connectomics approach. (8th April 2019) - Nestor, Liam J.; Behan, Brendan; Suckling, John; Garavan, Hugh
Abstract: Adolescence may be a period of increased vulnerability to the onset of drug misuse and addiction due to changes in developing brain networks that support cognitive and reward processing. Cannabis is a widely misused illicit drug in adolescence which can lead to dependence and alterations in reward‐related neural functioning. Concerns exist that cannabis‐related alterations in these reward networks in adolescence may sensitize behaviour towards all forms of reward that increase the risk of further drug use. Taking a functional connectomics approach, we compared an acutely abstinent adolescent cannabis‐dependent (CAN) group with adolescent controls (CON) on global measures of network topology associated with anticipation on a monetary incentive delay task. In the presence of overall superior accuracy, the CAN group exhibited superior global connectivity (clustering coefficient, efficiency, characteristic path length) during monetary gain anticipation compared with the CON group. Additional analyses showed that the CAN group exhibited significantly greater connectivity strength during monetary gain anticipation across a subnetwork that included mesocorticolimbic nodes involving both interhemispheric and intrahemispheric connections. We discuss how these differences in reward‐associated connectivity may allude to subtle functional alterations in network architecture in adolescent cannabis‐dependence that could enhance the motivation for nondrug reward during acute abstinence. Abstract : Network showing where the adolescent cannabis‐addicted group demonstrated significantly greater connectivity strength compared with a control group during reward anticipation on a monetary incentive delay task. This network was made up of mesocorticolimbic regions involving principally inter hemispheric connections, suggesting more long‐range routes of information exchange across the network during reward processing.